Constructing Hydrophobic Interface with Close‐Packed Coordination Supramolecular Network for Long‐Cycling and Dendrite‐Free Zn‐Metal Batteries. Issue 22 (2nd May 2022) - Tao, Zengren; Zhu, Yuanfei; Zhou, Zekun; Wang, Anding; Tan, Yuanming; Chen, Zhao; Yu, Minghao; Yang, Yangyi
Abstract: Commercialization of aqueous zinc‐metal batteries remains unrealistic due to the substantial dendrite growth and side reaction issues on the zinc anodes. It is highly demanded to develop easy‐to‐handle approaches for constructing stable, dense, as well as homogeneous solid anode/electrolyte interfaces. Herein, the authors construct the zinc anode interface with a close‐packed Zn‐TSA (TSA = thiosalicylate) coordination supramolecular network through the facile and up‐scalable wet‐chemical method. The hydrophobic Zn‐TSA network can block solvated water and establish a solid‐state diffusion barrier to well‐distribute the interfacial Zn 2+, thus inhibiting hydrogen evolution and zinc dendrite growth on the anode. Meanwhile, the Zn‐TSA network induces the formation of a uniform and stable solid electrolyte interphase composed of multiple inorganic‐organic compounds. This denser structure can accommodate and self‐heal the crack/degradation of the anode interphase associated with the repeated volume changes, and suppress the generation of detrimental by‐product, Zn x (OTF ‐ ) y (OH)2 x − y · n H2 O. Such a rationally fabricated anode/electrolyte interface further endows the assembled symmetric cells with superior plating/stripping stability for over 2000 h without dendrite formation (at 1 mA cm ‐2 and 1 mAh cm ‐2 ). Furthermore, this zinc anode has practical application in the Zn‐MoS2 and Zn‐V2 O5 full cells. This study provides a new train of thought for constructing the dense interface of zinc‐metal anode. Abstract : The hydrophobic Zn‐TSA network can block solvated water and establish a solid‐state diffusion barrier to well‐distribute the interfacial Zn 2+, thus inhibiting hydrogen evolution and zinc dendrite growth on the zinc anode, as well as suppressing the generation of detrimental by‐product. Meanwhile, Zn‐TSA induces the formation of a uniform and stable solid electrolyte interphase composed of multiple inorganic‐organic compounds.